Strengthening Early Childhood Motor Development through Structured Educational Play and Outdoor Learning - Irvan Kurniawan; Abdul Rahman; Febriyando Febr; Dwi Anantasari Gumohung; Suhadjerah Suhadjerah (CV Berkah Syahdin Trust, 2025)
Background: Motor development is a fundamental aspect of early childhood growth, influencing physical coordination, cognitive processes, and social interaction. However, in many early childhood education settings, particularly in geographically constrained areas, motor stimulation activities are often limited, less structured, and lack variation in instructional strategies. Aims: This community service initiative aims to strengthen early childhood motor development through structured educational play and outdoor learning activities. Methods: This program employed a participatory educational approach through direct engagement with teachers and children in an early childhood education institution. The implementation was carried out in three stages: initial observation and needs identification, structured intervention through educational play and outdoor activities, and reflective evaluation. The activities included movement-based exercises, fine motor skill stimulation, coordination games, and outdoor learning tasks. Data were collected through observation, documentation, and informal interviews, and analyzed using descriptive qualitative techniques. Results: The results indicate a significant improvement in children's participation and motor engagement during learning activities. Children demonstrated better coordination, balance, and fine motor control through activities such as bead stringing, geometric jumping, and coordinated movement exercises. The integration of outdoor learning also enhanced children's enthusiasm, interaction, and active involvement in the learning process. Conclusion: Structured educational play combined with outdoor learning effectively strengthens early childhood motor development. The implementation of this community service initiative provides a practical and applicable model for enhancing motor stimulation in early childhood education settings, particularly in areas with limited learning resources.